Valuation of deferred tax assets using a closed form solution - Silva, J.; Souto, N.; Pereira, J. (Using strategy analytics to measure corporate performance and business value creation, 2021)
Deferred tax asset (DTA) is a tax/accounting concept that refers to an asset that may be used to reduce future tax liabilities of the holder. It usually refers to situations where a company has either overpaid taxes, paid taxes in advance, or has carry-over of losses (the latter being the most common situation). DTAs are thus contingent claims, whose underlying assets are the company's future profits. Consequently, the correct approach to value such rights implies the use of a contingent claim valuation framework. The purpose of this chapter is to propose a precise and conceptually sound mathematical approach to value DTAs, considering future projections of earnings and rates, alongside the DTA's legal time limit. The authors show that with the proposed evaluation techniques, the DTA's expected value will be much lower than the values normally used in today's practice, and the company's financial analysis will lead to much more sound and realistic results.